Molecular dynamic simulation of patchoulol biotransformation - Norul Afwan, Kamarudin (2016)
Biotransformation is a branch of biotechnology process that produces the natural compound in the perfume industry naturally. Molecular dynamic simulation is a powerful tool which can be used to understand the molecule interaction at the molecular level through the measurement of the interaction strength between the molecules involved in the biotransformation process. The main objective of this paper is to present the development of a computer-aided simulation model for biotechnology process system. In this study, molecular dynamic (MD) simulation was used to investigate the effect of oxygen from dissolved oxygen gas and water molecule on the structural properties of an important chemical compound in patchouli oil, namely patchoulol, and also the interaction between them. Through the hydroxylation process, the hydroxylase enzyme catalyzes the formation of hydroxyl group on patchoulol by incorporating one atom of oxygen. This process is predicted to produce a new high value compound namely 10-hydroxypatchoulol. It is the intermediate compound for the formation of norpatchoulenol, which contributes significantly towards the patchouli oil scent. For better understanding and comparison, the structure of the patchoulol, oxygen and water was simulated in three systems, namely pure, binary and tertiary system. The Condensed-phase Optimized Molecular Potential of Atomic Simulation Studies, (COMPASS) force field was used to run the simulation. Simulations were performed for 1200 ps at 301 K and 1 atm for the liquid-solid state of the mixtures. Radial distribution function was analyzed from the trajectory files to measure the strength of intermolecular interaction between molecules. The result from the modelling simulation system shows the patchoulol is more interested to the dissolved oxygen gas in producing the van der Waals bond. The interaction is presented by sharp peak of RDF with the nearest distance at 3.75Å which it will initiate the formation of hydroxyl group in patchoulol molecule. Meanwhile the experimental work has undergone four stages, microorganism preparation, fermentation medium preparation, fermentation procedure and sample analysis. FTIR analysis covers the analysis from experimental and stimulated from the Gaussian Software analysis. By comparing of the experimental and stimulated data, it shows that there are match peaks at 3200cm-1, showing that the Hbonded in the hydroxyl group and at 1150cm-1, and that the C-O stretch, present as the primary alcohol. The result on both analysis showed the 10-hydroxypatchoulol might be present in the sample of product. GCMS has detected no appearance of 10-hydroxypatchoulol, but it detected 1(2H) Naphthalenone, octahydro-4,8 a-dimethyl-6- (1-methylethenyl) (4.alpha.,4a.beta., 6.alpha.,8a.beta.)- compound with chemical formula C15H24O. As a conclusion the objective from the modelling aspect was achieved, and produce the new compound instead of the predicted compound, 10hydropatchoulol in the experimental work.